Analisis Pengaruh Leverage, Ownership Structure, Firm Size Dan Mekanisme Corporate Governance Terhadap Kinerja Lingkungan Dengan Profitabilitas Sebagai Variabel Moderasi : Studi Empiris Pada Perusahaan Industri Dasar Dan Kimia Yang Terdaftar Di BEI - Meas, Albertina Dilianty Eka; Mulyadi, JMV; Sihite, Mombang (CV ODIS, 2024)
This research aims to analyze the influence of Leverage, Ownership Structure, Firm Size and Corporate Governance Mechanisms on Environmental Performance with Profitability as a Moderating Variable for Empirical Studies in Basic Industrial and Chemical Companies Listed on the BEI. The population in this research is basic industrial and chemical companies listed on the Indonesia Stock Exchange in 2017 - 2021. The research sample was taken from the population in the 2017 - 2021 period, namely 60 basic industrial and chemical companies listed on the IDX. The data analysis method in this research uses descriptive statistics and multiple linear regression analysis. The research results show that Leverage, Ownership Structure, Firm Size, and Profitability have a positive effect on Environmental Performance. Corporate Governance has no effect on Environmental Performance. Profitability does not significantly strengthen the relationship between Leverage and Environment Performance and the Ownership Structure relationship on Environmental Performance. Profitability does not significantly strengthen the relationship between firm size and environmental performance. Profitability does not significantly strengthen the relationship between Corporate Governance and Environmental Performance. Leverage, Ownership Structure, Firm Size, Corporate Governance, and Profitability together have an influence on Environmental Performance.